The Lights Of Sugarberry Cove - Webber, Heather S. (New York : Forge, a Tom Doherty Associates Book, 2021)
"The Lights of Sugarberry Cove is a charming, delightful story of family, healing, love, and small town Southern charm by USA Today bestselling author Heather Webber. Sadie Way Scott has been avoiding her family and hometown of Sugarberry Cove, Alabama, since she nearly drowned in the lake just outside her mother's B&B. Eight years later, Sadie is the host of a much-loved show about southern cooking and family, but despite her success, she wonders why she was saved. What is she supposed to do? Sadie's sister, Leala Clare, is still haunted by the guilt she feels over the night her sister almost died. Now, at a crossroads in her marriage, Leala has everything she ever thought she wanted-so why is she so unhappy? When their mother suffers a minor heart attack just before Sugarberry Cove's famous water lantern festival, the two sisters come home to run the inn while she recovers. It's the last place either of them wants to be, but with a little help from the inn's quirky guests, the sisters may come to terms with their strained relationships, accept the past, and rediscover a little lake magic"--.